Progress and challenges in integrated traditional Chinese and western medicine in China from 2002 to 2021 - Zhou, Man-Ci; Fei, Yu-Tong; Lai, Xiao-Zhen; Lan, Jian; Liu, Bo; Wang, Zhi-Wei; Fang, Hai; Liu, Jian-Ping; Rong, Hong-Guo (Frontiers in Pharmacology, 2024)
Objective: The World Health Organization advocated for enhanced integration of traditional medicine and complementary medicine into national healthcare systems across all countries. This study aims to explore the progress and challenges in integrated traditional Chinese and western medicine (ITCWM) in China over 20 years using nationwide data.: This cross-sectional study examined various facets of ITCWM in China in terms of policies, resources, services, and funding. National policy documents from 2009 onwards were retrieved from official websites of the Chinese government. Data on ITCWM resources, services and subsidies from 2002 to 2021 were extracted from the China Statistical Yearbooks of Chinese Medicine and China Health Statistical Yearbooks. Research fund projects with the ITCWM discipline were collected from the database of National Natural Science Foundation of China. A mixed method of both quantitative and qualitative approaches was employed to present a comprehensive overview of the collected data.Lastly, despite the Chinese government's emphasis on financial investment and related project funding for ITCWM, it remained lower than that allocated to TCM and western medicine.Conclusions: ITCWM played a pivotal role in China's healthcare system to advance individuals' health and well-being across the lifespan. In the future, China will provide further support to enhance ITCWM health resources and improve service capability, and the strategic integration of ITCWM into the broader healthcare system will play a crucial role in achieving universal health coverage and the Sustainable Development Goals.